Peramalan Jumlah Produksi Daging Sapi di Kabupaten Pesisir Selatan Menggunakan Metode Pemulusan Eksponensial Triple Tipe Brown - Pratama, Agung Putra (Journal of Mathematics UNP, 2025)
Beef is one of the sources of animal protein that has an important role in meeting the nutritional needs of the community. Beef production in South Coast Regency fluctuates every year, so an accurate forecasting method is needed to anticipate future production changes. This study aims to forecast the amount of beef production in Pesisir Selatan Regency using the Brown Type Exponential Smoothing method. The data used is secondary data from the Central Statistics Agency of South Pesisir Regency during the period 2006-2023. The results of the analysis show that the value of the optimal smoothing parameter is , with the smallest Mean Squared Error (MSE) value of 975,204,883,902. Based on the models obtained, the forecast results of beef production for 2024 to 2027 are 1,978,643 kg, 1,767,060 kg, 1,537,595 kg, and 1,290,248 kg.